KONSEP DESAIN VERTICAL GARDEN DI KAMPUNG TANGGUH KECAMATAN CURUG KOTA DEPOK - Atie Ernawati; Nurjannah Hamdani; Marselly Dwiputri (Universitas Indraprasta PGRI, 2022)
Depok City is one of the cities that experienced quite rapid development, the high population density in Depok City affects the needs and availability of urban facilities and infrastructure of Depok City, one of which is the green open space facilities that tend to decrease over time, especially in residential areas, One of the settlements affected by the lack of availability of RTH in Depok City is Kampung Tangguh. Kampung Tangguh is one of the residents' settlements located in Depok City. The conditions in Kampung Tangguh are densely populated housing with green open space that is owned very minimal. So that the residents of Kampung Tangguh are accustomed to gather and interact socially on the neighborhood road located in the settlement location. The purpose of this writing is to provide an alternative design of green open space on limited land in densely populated residential areas with case studies in Kampung Tangguh, Depok City. This research is carried out as a solution to deal with land limitations to provide green open space facilities in urban areas and design concepts are needed that can take advantage of limited space and potentially have aesthetic value, it is hoped that in addition to providing a green feel can also create the beauty of urban settlements, especially in Kampung Tangguh Depok City. The result of this study is a vertical garden design concept that can adapt the principle of green architecture to road corridors in densely populated urban settlements. The design concept can improve air quality in residential environments by greening vertical elements such as building walls and street furniture media and can provide improvements to open space conditions in kampung tangguh residential areas.